Metabolic, antioxidant and competence parameters for the embryonic development of bovine oocytes matured in vitro with l-carnitine - Jaramillo Bolívar, Natalia (2019)
The antioxidant and metabolic effect of L-carnitine (LC) was evaluated during the in vitro maturation of bovine oocytes on parameters associated with quality: relative amount of lipids, generation of reactive oxygen species (ROS), reduced glutathione levels (GSH), mitochondrial activity and competence for embryonic development after fertilization. The cumulus-oocyte complexes were matured for 24 h with and without L-C (3.8 mM), and incubated with the specific fluorophore for each parameter, Nile Red (lipids), Dichlorofluorescein diacetate (EROs), Monoclorobimane (GSH), Mitotracker Green (mitochondria). The intensity of the fluorescence was analyzed with the ImageJ software and normalized to the control group of matured oocytes without L-Carnitine. To determine the competence of the oocyte for embryonic development, the matured oocytes were fertilized and cultured for 8 days. In oocytes matured with L-C a decrease of 8.1% of the relative amount of lipids and 41.6% in the generation of EROs was found, while mitochondrial activity increased by 160% with respect to control, plus improved the kinetics and percentage of blastocysts. However, GSH levels were not affected by L-C. The results support the beneficial effect of L-C during the in vitro maturation of the bovine oocyte to improve antioxidant and metabolic parameters that are reflected in the in vitro production of bovine embryos.